2014
DOI: 10.1210/jc.2013-3589
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Within the Normal Range and the Risk of Depression: A Population-Based Cohort Study

Abstract: Elderly persons with low-normal TSH levels have more concurrent depressive symptoms as well as a substantially increased risk of developing a depressive syndrome in the subsequent years. This study identifies low-normal TSH as an important risk factor for depression in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 36 publications
2
66
2
1
Order By: Relevance
“…In euthyroid subjects without thyroid disease, depression, anxiety, or cognitive decrements have been linked to variations in TSH or free thyroxine (fT4) levels (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, the correlations have shown improvements or decrements with higher or lower thyroid function, depending on the report.…”
Section: Introductionmentioning
confidence: 99%
“…In euthyroid subjects without thyroid disease, depression, anxiety, or cognitive decrements have been linked to variations in TSH or free thyroxine (fT4) levels (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, the correlations have shown improvements or decrements with higher or lower thyroid function, depending on the report.…”
Section: Introductionmentioning
confidence: 99%
“…FT4 levels within the normal range in a few cross-sectional studies (13,14,16). However, the correlations were in different directions depending on the report, and recent large and wellconducted studies found no correlations between TSH levels and depression or anxiety (20,22,24).…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, no prospective studies have examined the effects of variations in thyroid function within the reference range on quality of life over time. A few prospective studies have correlated baseline thyroid function within the reference range with the development of depressive symptoms (16,20,22). Two of these studies failed to find an association (20,22), while the third reported that lower TSH levels within the reference range were associated with more depressive symptoms and incident diagnoses of clinical depression (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations